Arbuscular mycorrhizal inoculation in avocado rootstocks cv ‘Hass’ in nurseries of Michoacán, Mexico - Carreón Abud Yazmín; Aguirre Paleo, Salvador; Gavito, Mayra E.; Mendoza Solís Dorian Javier; Juárez Chávez Raúl; Martínez Trujillo Miguel; Trejo Aguilar, Dora (Revista Mexicana de Ciencias Agrícolas, 2018)
The aim of this study was to evaluate the performance of twelve inoculants of arbuscular mycorrhizal fungi (AMF) in the development of avocado rootstock cv. ‘Hass’ in the nursery stage. The experiment was conducted in Uruapan, Michoacán, Mexico, using 60-days-old, newly grafted rootstocks. The 12 treatments were in a completely randomized design with 6 replications: A) Gigaspora gigantea; B) Acaulospora delicata; C) Rhizophagus fasciculatus (foreign); D) MTZ1-UV Consortium from Veracruz; E) Rhizophagus fasciculatus; F) Rhizophagus irregularis 28-A; G) Native AMF community; H) Rhizophagus irregularis (MUCL); I) Rhizophagus fasciculatus + Azospirillum; J) Sclerocystis aff. rubiformis; K) Acaulospora laevis; L) Scutellospora pellucida; M) Control. Plant height, stem diameter and number of leaves were measured every two weeks for 5 months, after which plants were harvested and shoot and root dry weight were also measured. Periodical measurements showed that Acaulospora delicata and the control performed better in terms of plant height, Scutellospora pellucida in terms of stem diameter and the control in the number of leaves along the experiment. At harvest, plants inoculated with Rhizophagus intraradices 28-A and Scutellospora pellucida had twice as large shoot and root weights as the rest of plants. We conclude that stem collar inoculation of recently grafted plants showed clear responses to inoculation with efficient strains of mycorrhizal fungi even though it took over six months before differences became evident.